(untitled) (Journal of the Sociology and Theory of Religion, 2025)
The relationship between religion and economics has been a topic of interest throughout history among economists, historians and sociologists, as well as the subject of many debates and studies. Religion has influenced the way society is organized and structured, including the economy, and has had a significant impact on the way people think about money, work and property.